PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI DENGAN PEMBERIAN INSENTIF SEBAGAI VARIABEL MODERASI - Indra Lestari Sumbung; Syaikhul Falah; Alfiana Antoh (Universitas Cenderawasih, 2017)
This research attempts to: (1) is there a significant relation between the incentives and the performance of civil servants at the secretariat of the Jayawijaya regency, (2) is there a significant relation between the discipline and the performance of civil servants in secretariat of Jayawijaya regency, (3) is there a significant relation in motivation to the performance of civil servants by the provision of incentives for moderating variable, and (4) is there a significant relation between the discipline to the performance of civil servants by the provision of incentives for moderating variable. The data used was primary data from the questionnaire distributed to civil servants within the regional secretariat of Jayawijaya regency year of 2015 with 55 of respondents. The analysis method is moderated regression analysis (MRA). Based on the results known that working motivation had a positive and significant impact on working performance of employees; discipline have a negative and insignificant influence on the performance of civil servants; working motivation moderated by the provision of incentives or the granting of additional income have a negative and insignificant influence on the performance of civil servants; the discipline that moderated by the provision of incentives or the granting of additional income had a positive impact but not significantly to working performance of employees. Keyword: motivation, discipline, incentive, performance, Jayawijaya regency